2015
DOI: 10.1111/eip.12203
|View full text |Cite
|
Sign up to set email alerts
|

Use of medication algorithms in first episode psychosis: a naturalistic observational study

Abstract: Initial medical intervention followed international standards, but the physicians failed to adhere to algorithms in their follow-up of medication regimes. Adherence was associated with outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The applicability of clinical practice guidelines in psychiatry has been studied during recent years, including trying to identify barriers to guideline adherence. 31 34 Some proposed barriers are physician related, such as lack of awareness or familiarity, lack of agreement and concerns about control over professional practice. There are also patient-related barriers such as nonadherence and reluctance, clarity and complexity of guidelines, and environmentally related barriers such as resources and facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of clinical practice guidelines in psychiatry has been studied during recent years, including trying to identify barriers to guideline adherence. 31 34 Some proposed barriers are physician related, such as lack of awareness or familiarity, lack of agreement and concerns about control over professional practice. There are also patient-related barriers such as nonadherence and reluctance, clarity and complexity of guidelines, and environmentally related barriers such as resources and facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we should note that adherence to prescribed medication is a major challenge for first episode patients (47, 48). In addition, previous studies have found that physicians’ adherence to guidelines is adequate in the initial phase of treatment but reduces over time (49). The recommendation of low dosages for first-treatment phases also pertains to the acute phases of illness, and previous studies indicate that lower acute phase dosages is an achievable goal (50).…”
Section: Discussionmentioning
confidence: 99%
“…The acute treatment algorithm recommends only aripiprazole as a first-line antipsychotic agent, which is different from other treatment algorithms for first-episode schizophrenia/psychosis (Agid et al, 2011;Drosos et al, 2020;Yeisen et al, 2016;Yoshimura et al, 2019). We prioritized minimizing adverse effects over maximizing efficacy for the first place, because long-term treatment with antipsychotics is needed to prevent relapse and exacerbation in patients with schizophrenia (Leucht et al, 2012;Takeuchi et al, 2017).…”
Section: Pharmacological Treatment Algorithm For the Maintenance Phase Of First-episode Schizophreniamentioning
confidence: 99%
“…A systematic review identified only a few treatment algorithms for schizophrenia in general, although a substantial number of treatment guidelines are available. To our knowledge, there have been only three and one treatment algorithms designed specifically for first-episode schizophrenia (Agid et al, 2011;Drosos et al, 2020;Yoshimura et al, 2019) and psychosis (Yeisen et al, 2016), respectively. Moreover, all the algorithms were used for acute treatment, but not for maintenance treatment.…”
Section: Introductionmentioning
confidence: 99%